(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The evaluation of plants’ ability to resist pollution was conducted by studying two distinct plant species, Swietenia mahagonia and Polyalthia longifolia, obtained near the urban roadsides in Dhaka during the winter season. The air pollution tolerance index (APTI) was assessed for both Polyalthia longifolia and Swietenia mahagoni. Between the two species, Polyalthia longifolia exhibited the highest air pollution tolerance index (APTI 12.54), indicating its lower sensitivity towards pollution. On the other hand, Swietenia mahagoni (APTI 12.27) demonstrated a comparatively higher sensitivity to pollutants. Polyalthia longifolia had the highest total chlorophyll concentration (TCC) (1.080 mg/g), relative water content (RWC) (88.50%), pH value (6.73), ascorbic acid concentration (ACC) (4.303). On the other hand, Swietenia mahagoni showed the lowest scores across almost all the indicators (except ACC: 5.44), demonstrating the most pollutant-sensitive species. The assessment of plants in relation to their capacity to withstand air pollution is crucial due to their role as a pollution sink. Consequently, planting species that exhibit tolerance to pollution in contaminated regions can provide several environmental advantages. Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 1-10